2010
DOI: 10.1073/pnas.0910872107
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol trafficking is required for mTOR activation in endothelial cells

Abstract: Mammalian target of rapamycin (mTOR) constitutes a nodal point of a signaling network that regulates cell growth and proliferation in response to various environmental cues ranging from growth factor stimulation to nutrients to stress. Whether mTOR is also affected by cholesterol homeostasis, however, has remained unknown. We report that blockade of cholesterol trafficking through lysosome by a newly identified inhibitor of angiogenesis, itraconazole, leads to inhibition of mTOR activity in endothelial cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
184
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(202 citation statements)
references
References 39 publications
13
184
0
Order By: Relevance
“…Similarly, our study showed that treatment with TO901317 in goose hepatocytes promoted mRNA expression of S6K. Otherwise, one previous study suggested that cholesterol trafficking is required for mTOR activation in endothelial (Xu et al, 2010), which confirmed the role of mTOR in cholesterol biosynthesis. Huwait et al showed that the LXR agonists-induced ABCA1 promoter activity was inhibited by the expression of dominant negative forms of the components of the PI3K pathways (Huwait et al, 2011).…”
Section: General Remarkssupporting
confidence: 86%
“…Similarly, our study showed that treatment with TO901317 in goose hepatocytes promoted mRNA expression of S6K. Otherwise, one previous study suggested that cholesterol trafficking is required for mTOR activation in endothelial (Xu et al, 2010), which confirmed the role of mTOR in cholesterol biosynthesis. Huwait et al showed that the LXR agonists-induced ABCA1 promoter activity was inhibited by the expression of dominant negative forms of the components of the PI3K pathways (Huwait et al, 2011).…”
Section: General Remarkssupporting
confidence: 86%
“…Numerous studies have indicated a critical involvement of cholesterol in the differentiation and function of a variety of cell types, including endothelial cells, cardiac muscle cells, macrophages, and osteoblasts (57)(58)(59). It is well known that cholesterol is a major component of the plasma membrane, and especially of lipid rafts (36 -39).…”
Section: Discussionmentioning
confidence: 99%
“…Itraconazole inhibits AKT (protein kinase B)/mechanistic target of rapamycin (mTOR) signaling in human umbilical vein endothelial cells (HUVECs), glioblastoma, endometrial carcinoma (EC) and melanoma cells (10)(11)(12)(13)(14). Inhibition of Hedgehog signaling was observed in basal cell carcinoma, medulloblastoma, pleural mesothelioma, breast cancer and melanoma cells (9,(14)(15)(16)(17), but not in EC cells (13).…”
Section: Preclinical Datamentioning
confidence: 99%